2021
DOI: 10.1097/icu.0000000000000765
|View full text |Cite
|
Sign up to set email alerts
|

Update on corneal collagen crosslinking for ectasia

Abstract: Purpose of reviewCorneal collagen crosslinking (CXL) is a minimally invasive treatment that can stabilize corneal ectatic disorders including keratoconus, pellucid marginal degeneration, or postrefractive surgery ectasia. The benefits of CXL have been well documented. New research is focused on modifying current treatment protocols with the goals of maximizing corneal stability while also shortening overall procedure time. Recent findingsAccelerated CXL protocols have the goal of delivering the same ultraviole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 43 publications
1
8
0
Order By: Relevance
“…It is certain that a refractive procedure is safer for patients who have undergone a cornea transplant than another transplant, which carries a much greater burden and poses a higher risk for the patient, especially as refractive procedures do not require corneal tissue [ 21 , 22 ]. In refractive surgery, the most important evaluated parameters are uncorrected vision acuity (UCVA), which is visual acuity expressed in D without any correction, and best-corrected vision acuity (BCVA), which is visual acuity expressed in D after the application of an appropriate vision correction, determined during the eye examination [ 23 25 ]. After the laser vision correction procedure, the UCVA value corresponds to the visual acuity the patient would have achieved after correction before the procedure [ 23 25 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is certain that a refractive procedure is safer for patients who have undergone a cornea transplant than another transplant, which carries a much greater burden and poses a higher risk for the patient, especially as refractive procedures do not require corneal tissue [ 21 , 22 ]. In refractive surgery, the most important evaluated parameters are uncorrected vision acuity (UCVA), which is visual acuity expressed in D without any correction, and best-corrected vision acuity (BCVA), which is visual acuity expressed in D after the application of an appropriate vision correction, determined during the eye examination [ 23 25 ]. After the laser vision correction procedure, the UCVA value corresponds to the visual acuity the patient would have achieved after correction before the procedure [ 23 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…In refractive surgery, the most important evaluated parameters are uncorrected vision acuity (UCVA), which is visual acuity expressed in D without any correction, and best-corrected vision acuity (BCVA), which is visual acuity expressed in D after the application of an appropriate vision correction, determined during the eye examination [ 23 25 ]. After the laser vision correction procedure, the UCVA value corresponds to the visual acuity the patient would have achieved after correction before the procedure [ 23 25 ]. This explains why the UCVA values before and after a successful procedure are significantly different from each other, while the corresponding BCVA values are not statistically significant [ 23 25 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent systematic literature reviews [ 1 , 27 , 28 ] found that the clinical outcomes and safety of conventional and accelerated CXL protocols were comparable. In addition, pulsed mode may increase the long-term efficacy and safety of the accelerated protocols.…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15][16] To reduce treatment times, variations in CXL protocols have arisen. [13][14][15][16][17] Different riboflavin induction times have been used across the globe. To the best of our knowledge, there are no published studies on the comparative effectiveness of different riboflavin induction times during CXL.…”
mentioning
confidence: 99%